The university system of Sri Lanka : vision and reality - De Silva, K. M.; Peiris, G. H.; International Centre for Ethnic Studies; Leverhulme Trust; Friedrich-Ebert-Stiftung (Sri Lanka) (New Delhi : Macmillan India Ltd., 1995)
Revision of papers originally presented at two workshops held in Kandy in August and November 1991.
"International Centre for Ethnic Studies, Kandy, Sri Lanka in association with the Leverhulme Trust, London, and, Friedrich Ebert Stiftung, Colombo, Sri Lanka."
Keywords: University of Peradeniya -- History; Universities and colleges -- Sri Lanka -- History; Higher education and state -- Sri Lanka -- History